2009
DOI: 10.3945/jn.109.113126
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Biomarkers and Liver and Kidney Function Are Not Altered in Postmenopausal Women after Ingesting an Elderberry Extract Rich in Anthocyanins for 12 Weeks ,

Abstract: Growing evidence supports a cardio-protective role for anthocyanins; however, there is limited evidence on their efficacy and safety following the consumption of relatively high but dietarily achievable doses in humans. We conducted a parallel-designed, randomized, placebo-controlled study to examine the effect of chronic consumption of anthocyanins on biomarkers of cardiovascular disease (CVD) risk and liver and kidney function in 52 healthy postmenopausal women (n = 26 in treatment and placebo groups). Volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
137
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 26 publications
7
137
1
Order By: Relevance
“…Genistein increases the rate of b-oxidation through increasing the activity of succinate dehydrogenase and CPT-1 in OVX rats (Choi et al 2012). However, in postmenopausal women, 12-week consumption of elderberry extracts rich in anthocyanins (500 mg/day) did not change biomarkers of liver function, although the plasma concentrations of anthocyanin metabolites of the elderberry treatment group were greater (P = 0.02) than that of the control at week 12 of the treatment (Curtis et al 2009). …”
Section: Discussionmentioning
confidence: 89%
“…Genistein increases the rate of b-oxidation through increasing the activity of succinate dehydrogenase and CPT-1 in OVX rats (Choi et al 2012). However, in postmenopausal women, 12-week consumption of elderberry extracts rich in anthocyanins (500 mg/day) did not change biomarkers of liver function, although the plasma concentrations of anthocyanin metabolites of the elderberry treatment group were greater (P = 0.02) than that of the control at week 12 of the treatment (Curtis et al 2009). …”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the study should have control groups for comparison. However, Curtis et al [119] indicate the consumption of 500 mg/day of elderberry extract for 12 weeks is ineffective in reducing the risk of CVD in healthy postmenopausal women. There is also no change in metabolic processing following 12 weeks of elderberry intake compared with acute intake [120].…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…6 Anthocyanin-containing intervention studies supporting antihypertensive effects lasted 6 weeks, 4,5 whereas a study not supporting antihypertensive effect lasted 12 weeks. 22 In the flavonoid meta-analysis, median treatment duration was 2-6 weeks, and studies of longer duration indicated reduced effect sizes compared with studies of shorter duration. 3 Interestingly, we found that absolute Finometer BPs were significantly lower at certain intervals during periods of supine rest, and that areas under the curve for Finometer BPs during the stress testing were significantly lower following anthocyanin treatment.…”
Section: Discussionmentioning
confidence: 99%